Application of Overall Equipment Effectiveness for Optimizing Ventilator Reliability in Intensive Care Units and Emergency Departments - Khelood A. Mkalaf; Rami Hikmat Al-Hadeethi; Peter Gibson (Journal of Techniques)
Healthcare organizations seek to offer a comprehensive medical services system framework with safety and high quality. This needs continuously developing integrated governance systems that provide safe, reliable, and maintaining high-quality care and value-based care for patients. In addition to improving access to health services in time, increasing efficiencies in providing medical services, reducing the risk-based medical services, and selecting a suitable maintenance policy for maintaining the medical devices. This paper adopted a quantitative analysis method based on Reliability-Based Maintenance (RCM) to comprehensively evaluate the overall medical equipment's effectiveness. RCM is an integrated approach to continuous improvement of the maintenance programs because it can predict early medical equipment failure and determine the mean time between failures. It also assesses the risk level to the patient's life in case of a medical equipment breakdown while provisioning medical services. This study targeted biomedical engineering, intensive care units, and emergency departments at 24 public hospitals in a top 20 OECD country. It selected these departments due to the rise in the rate of patients needing ventilator equipment availability during COVID-19, risk based on the sudden breakdown of the ventilator machines, and increasing the annual budget percentage required to provide medical services, where 239 of the ventilator equipment were investigated. Staff Experience-based Evidence was adopted to collect data by interviewing staff and distributing the survey. The study found that the average OEE for ventilator devices in Intensive Care Units and Emergency Departments was 63%. The device's performance was rated at 65%, while its availability and quality rate were both rated at 100%. These findings suggest that the use of the OEE metric has improved ventilator device reliability and performance in selected hospitals. The OEE metric may have potential benefits for improving the performance of other medical devices as well.